Evolution of the Islamic Judicial System: Justice in the Governance of Caliph ‘Umar Ibn Al-Khaṭṭāb - Amin, Muhamad; Murdiono, Murdiono; Sarimov, Renat (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Justice in Islamic law has its significance and its inception dates back to the appointment of Prophet Muhammad. From that moment, the Prophet Muhammad assumed the role of the first judge in the Islamic world, overseeing and deciding all cases presented. Following the death of the Prophet, the authority of justice was transitioned to the caliphs. In so doing, the caliphs consistently adhered to the guidance of the Quran, the Sunnah, and Ijma. In addition to them, judges are individuals who possess a deep understanding of the Quran, the Sunnah, and Ijma. Compensation for judges is determined in accordance with regulations set by the caliph. Judges emphasize a commitment to justice in their rulings. The legacy of a just judicial system within the Islamic legal framework continued to thrive through upholding the foundations of the Quranic teachings and the Prophet's traditions.